Customer perspectives on water quality, safety, and service failure risks. Issue 8 (1st August 2013) - Chalak, Ali; Reid, Scott; Silcock, Martin; Abiad, Mohamad G.
Abstract : Mixed logit models offer a useful framework for understanding variations in customers' attitudes toward service failure risks. However, assumptions of normality could be unrealistic in cases in which attitudes are bounded by zero and risk indifference is common among customers. This article presents findings from a choice experiment that gauged customers' attitudes toward risks associated with water quality, safety, and service failures. The preferred model was specified with bounded and flexible distributions of parameters to accommodate plausible distributional patterns. Results suggest that whereas customers are relatively indifferent to lower‐risk occurrences such as boil‐water notices, higher‐risk situations such as "don't use" notices cause a shift to "risk‐dislike." Moreover, results indicated that indifference is more pronounced among customers who have previously experienced water safety failures. As study results highlight, communication and messaging strategies that mimic experiences of distress caused by water service failures can serve as effective tools for intervention and mitigation.